Análisis y propuesta del uso de las TIC’s como apoyo académico para una mayor inclusión de las personas con discapacidad visual y auditiva en la Universidad Técnica de Babahoyo. - Parra Suarez, Dennis Brigette (2022)
Information and Communication Technologies (ICT) refer to the study, design, development, implementation and support of computer information systems, especially computer software applications. To date, little is known about the extent to which ICTs are accessed and used to support learning among students with visual and hearing impairments at the Technical University of Babahoyo. This case study called "Analysis and proposal for the use of ICTs as academic support for greater inclusion of people with visual and hearing disabilities at the Technical University of Babahoyo. The use of available technologies is considered as the main tool for the implementation of inclusion and participation. Technology can be divided into three categories: assistive technology, accessibility technology, and universal design. ICT favors the adaptation of the educational process to the characteristics, interests and needs of the students, helping them to actively participate in achieving their learning objectives. Teachers seem to have a positive attitude towards the use of ICT and in recent years they have acquired more knowledge in this field. This case study has as a proposal the inclusion of ICT resources as academic support for people with visual and hearing disabilities at the Technical University of Babahoyo. With regard to assistive technology, teachers are beginning to become familiar with special devices and software.